👤

calculati respectand regulile invatate.
d) 9*(101*1+111:1)-[85-7*(36:9+63:9)]
e) 3+6*[30+6*(3+5*6)-28]-3
f) 2+2*[2+3*(2+202:2-306:3)]


Răspuns :

d) 9 x (101 + 111) - [85-7 x (4 + 7)
   - 9 x 212 - (85- 7 x 11)
    - 9 x 212 - (85 - 77)
    - 9 x 212 - 8
   - 1908 - 8
    - 1900
d) 9 x(101x1+111:1)-([85-7x(36:9+63:9)]
9x(101+111)-[85-7x(4+7)]=
9x212-(85-7x11)
1908-(85-77)=
1908-8=1900

e)3+6x[30+6x(3+5x6)-28]:3=
3+6x[30+6x(3+30)-28]:3=
3+6x(30+6x33-28):3=
3+6x(30+198-28):3=
3+6x200:3=
3+1200:3=
3+400=403

f)2+2x[2+3x(2+202:2-306:3)]=
2+2x[2+3x(2+101-102)]=
2+2x[2+3x(103-102)]=
2+2x(2+3x1)=
2+2x(2+3)=
2+2x5=
2+10=12